Functional Conservation of a Developmental Switch in Mammals since the Jurassic Age. (8th October 2018) - Mookerjee-Basu, Jayati; Hua, Xiang; Ge, Lu; Nicolas, Emmanuelle; Li, Qin; Czyzewicz, Philip; Zhongping, Dai; Peri, Suraj; FuxmanBass, Juan I; Walhout, Albertha J M; Kappes, Dietmar J
Abstract: ThPOK is a "master regulator" of T lymphocyte lineage choice, whose presence or absence is sufficient to dictate development to the CD4 or CD8 lineages, respectively. Induction of ThPOK is transcriptionally regulated, via a lineage-specific silencer element, Sil ThPOK . Here, we take advantage of the available genome sequence data as well as site-specific gene targeting technology, to evaluate the functional conservation of ThPOK regulation across mammalian evolution, and assess the importance of motif grammar (order and orientation of TF binding sites) on Sil ThPOK function in vivo . We make three important points: First, the Sil ThPOK is present in marsupial and placental mammals, but is not found in available genome assemblies of nonmammalian vertebrates, indicating that it arose after divergence of mammals from other vertebrates. Secondly, by replacing the murine Sil ThPOK in situ with its marsupial equivalent using a knockin approach, we demonstrate that the marsupial Sil ThPOK supports correct CD4 T lymphocyte lineage-specification in mice. To our knowledge, this is the first in vivo demonstration of functional equivalency for a silencer element between marsupial and placental mammals using a definitive knockin approach. Finally, we show that alteration of the position/orientation of a highly conserved region within the murine Sil ThPOK is sufficient to destroy silencer activity in vivo, demonstrating that motif grammar of this "solid" synteny block is critical for silencer function. Dependence of Sil ThPOK function on motif grammar conserved since the mid-Jurassic age, 165 Ma, suggests that the Sil ThPOK operates as a silenceosome, by analogy with the previously proposed enhanceosome model.